2022
DOI: 10.1088/1755-1315/1054/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Cytotoxicity Effects of Selected Nanoparticles: A Review

Abstract: The appreciable development in nanotechnology has drawn the attention of several researchers cutting across different fields. However, some nanoparticles have been identified to possess harmful effects on humans and the environment. Hence, putting these cause and effect patterns into context is highly required for future research and discussions about nanotechnology. This study reviewed existing literature on the toxicity and cytotoxicity effects of some nanoparticles to compare reaction patterns. Many kinds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This is because higher levels of positively charged NPs result in stronger electrostatic interactions with negatively charged cell membranes, promoting increased endocytic uptake and accumulation within cellular components, ultimately leading to heightened cellular toxicity. [15,37,38] In general, an increase in hydrodynamic diameter reduces toxicity, as larger size of NPs reduce the uptake of NPs. On the other hand, smaller NPs have greater potential for uptake and higher surface area to volume ratio contributing to higher toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…This is because higher levels of positively charged NPs result in stronger electrostatic interactions with negatively charged cell membranes, promoting increased endocytic uptake and accumulation within cellular components, ultimately leading to heightened cellular toxicity. [15,37,38] In general, an increase in hydrodynamic diameter reduces toxicity, as larger size of NPs reduce the uptake of NPs. On the other hand, smaller NPs have greater potential for uptake and higher surface area to volume ratio contributing to higher toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Another effect of nanoparticles is their toxicity and cytotoxicity in healthy cells [ 78 ]. Unavoidably, nanoparticles are potentially toxic to the human body.…”
Section: Synthesis Methods Of Npsmentioning
confidence: 99%
“…Hence, the research on this topic continues to rise. Several studies have revealed that the toxicity of nanoparticles is related to size, shape, and concentration [ 78 , 80 , 81 ]. However, surface coating has been one of the most popular surface modification strategies to reduce the possible toxicity of nanoparticles, which is reversible using non-covalent modification [ 67 ].…”
Section: Synthesis Methods Of Npsmentioning
confidence: 99%
“…In a rat macrophage cell line, it was discovered that rod-shaped Fe2O3 NPs produced significantly stronger cytotoxic reactions than sphere-shaped Fe2O3 NPs. These responses included higher levels of necrosis, ROS production, inflammatory response, and lactate dehydrogenase (LDH) leakage (Odaudu et al 2022). Eventually, it was shown that rod-shaped CeO2 NPs were more hazardous to macrophage cells than octahedron or cubic particles.…”
Section: Shape Of Nanoparticlesmentioning
confidence: 99%